PENGARUH PENGAWASAN KEPALA DINAS TERHADAP KINERJA PEGAWAI TIM PEMUNGUTAN RETRIBUSI PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN INDRAMAYU: The Effect of the Head of Department's Supervision on Employee Performance in the Retribution Collection Team at the Department of Public Works and Spatial Planning, Indramayu Regency - Maulana Malik; Zaki Kurniawan; Rohadin Rohadin (Jurnal Investasi, 2025)
This study aims to analyze the influence of department head supervision on the performance of employees on the retribution collection team at the Public Works and Spatial Planning (PUPR) Department of Indramayu Regency. Supervision is a crucial managerial function that determines the effectiveness of achieving public organization goals. Through targeted supervision, leaders can ensure task execution meets established standards and work targets. This study used a descriptive quantitative approach with a survey method. The study population was all 45 employees on the retribution collection team at the PUPR Department of Indramayu Regency, and the entire population was sampled (census). Primary data were obtained through the distribution of questionnaires compiled based on supervision indicators according to Terry (2009): standard setting, implementation measurement, and corrective action. Meanwhile, employee performance was measured based on indicators of effectiveness, efficiency, responsibility, and punctuality. The results indicate that department head supervision has a positive and significant effect on the performance of employees on the retribution collection team. The correlation coefficient of 0.712 indicates a strong relationship between the two variables, while the determination value (R² = 0.507) indicates that department head supervision contributes 50.7% to the variation in employee performance. This means that the better the supervision system implemented, the higher the employee performance in carrying out regional retribution collection duties. The most dominant supervisory factors include assertiveness in providing direction, clarity of work standards, and consistency in periodic evaluations of employee performance. This study concludes that the success of employee performance within the Indramayu Regency Public Works and Public Housing Agency is determined not only by technical skills but also by the quality of supervision conducted by leaders. The main recommendations of this study are the need to improve the participatory supervision system and the implementation of two-way feedback to increase effective communication between leaders and subordinates in achieving public service targets.